Mobile Robot for Life Science Automation. (10th July 2013) - Liu, Hui; Stoll, Norbert; Junginger, Steffen; Thurow, Kerstin
The paper presents a control system for mobile robots in distributed life science laboratories. The system covers all technical aspects of laboratory mobile robotics. In this system: (a) to get an accurate and low-cost robot localization, a method using a StarGazer module with a number of ceiling landmarks is utilized; (b) to have an expansible communication network, a standard IEEE 802.11g wireless network is adopted and a XML-based command protocol is designed for the communication between the remote side and the robot board side; (c) to realize a function of dynamic obstacle measurement and collision avoidance, an artificial potential field method based on a Microsoft Kinect sensor is used; and (d) to determine the shortest paths for transportation tasks, a hybrid planning strategy based on a Floyd algorithm and a Genetic Algorithm (GA) is proposed. Additionally, to make the traditional GA method suitable for the laboratory robot's routing, a series of optimized works are also provided in detail. Two experiments show that the proposed system and its control strategy are effective for a complex life science laboratory.